FOSTERING TOLERANCE IN HISTORY LEARNING THROUGH THE STUDY OF NUSANTARA KINGDOMS - Dewi Sartika, Ropita (CV. Fahr Publishing, 2024)
This study aims to analyze the cultivation of tolerance attitudes in history learning through the material on ancient kingdoms in the Nusantara and to assess the impact of history learning on students' tolerance attitudes in daily life. The research employs a literature review method. Data sources used in this study include books, journals, and historical documents relevant to the material on Nusantara kingdoms. The data analysis in this study uses a descriptive-qualitative approach to identify elements of tolerance in historical materials and learning strategies that can be applied in the classroom. The research findings indicate that fostering tolerance attitudes in history learning about Nusantara kingdoms can be achieved by integrating tolerance values into classroom learning materials. The use of discussion methods, case studies, and collaborative projects can be effective in this process. Teachers play a crucial role in creating an engaging learning environment by emphasizing the importance of respecting diversity that has existed since the era of Nusantara kingdoms. Historical materials on Nusantara kingdoms are rich in tolerance values relevant for application in modern educational contexts for students.